Board and audit committee characteristics and their influence on corporate social responsibilities disclosures in Malaysian companies - Abdul Wahid Mohd Kassim; Raman Noordin; Junainah Jaidi; Sulaiman Tahajuddin (IJRMBS 2014, 2020)
This paper investigates the link between Board and Audit Committee characteristics and the quantity of CSR in annual reports. This study used content analysis and a dataset from Bursa Malaysia public listed companies. Results based on the full regression model with four variables indicated that only one variable, Malay Dominated Board is associated with the extent of CSRD. The two other predictive variables, Audit Committee dominated by Malay directors and the ethnicity of the Audit Committee’s Chairperson were found to be significant but not in the predicted direction. While, the variable the Board is chaired by Malay, however, was found to be insignificant when regression analyses are performed.